The American Landscape: from an Ideological to an Ecological Object in Oxbow Archive by Joel Sternfeld - Helena Lamouliatte (Transatlantica)
American photographer Joel Sternfeld (born 1944) published Oxbow Archive in 2008, a book comprising 77 photographs that were taken over the course of a year and a half, between July 2005 and March 2007, and depicting a place called the East Meadows, located on the East side of the Connecticut river bend. Sternfeld chose the very place that was represented in Thomas Cole’s famous View from Mount Holyoke, Northampton, Massachusetts, after a Thunderstorm—The Oxbow (1836). Sternfeld obviously resorts to intericonicity, but he has chosen to reverse the perspective completely, both from a visual and ideological viewpoint. Indeed, Sternfeld’s images are no longer about the visual domination and appropriation of landscape in order to praise the conquest of the American territory; they put forward a new conception of the wilderness, based on aesthetic, political and ecological grounds. Sternfeld doesn’t blatantly criticize the way men claim ownership of natural spaces, but prefers to use a rigorous and elaborate aesthetic framework, combined with a serial mode of representation that only shows traces of human presence. The series walks a fine line between the utopian / dystopian modes, without ever losing sight of the tension between the celebration of the American pastoral and ecological concerns. His work therefore can be analyzed through the prism of ecocriticism.